2020
DOI: 10.2217/fca-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Management of Oral Factor Xa inhibitor-related Bleeds With Reversal Or Replacement Agents Including Andexanet Alfa and four-factor Prothrombin Complex Concentrate: A Multicenter Study

Abstract: Aim: We describe the real-world utilization and outcomes associated with managing oral factor Xa inhibitor (FXai)-related major bleeds. Materials & methods: Electronic records from 45 US hospitals were queried (ICD-10-CM billing codes D68.32, T45.515x or T45.525x) to identify major bleed hospitalizations related to FXai use. Patient demographics, bleed type (intracranial hemorrhage, gastrointestinal, critical compartment, traumatic, other), FXai taken, reversal or replacement agents administered (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 21 publications
1
38
0
3
Order By: Relevance
“…After the exclusion of these 2 studies, the data on the comparison of 4F-PCC and AA were derived from 8 retrospective studies. [35][36][37][39][40][41][42]44 We found that 4F-PCC had a comparable proportion of successful…”
Section: Subanalysismentioning
confidence: 60%
“…After the exclusion of these 2 studies, the data on the comparison of 4F-PCC and AA were derived from 8 retrospective studies. [35][36][37][39][40][41][42]44 We found that 4F-PCC had a comparable proportion of successful…”
Section: Subanalysismentioning
confidence: 60%
“…Two other retrospective analyses have associated a decreased incidence of mortality with andexanet alfa compared to 4F-PCC. 31,32 However, a metaanalysis associated andexanet alfa with a nonsignificantly increased hospital mortality yet a numerically lower 30-day mortality. 38 A randomized prospective study is needed to further examine these associations.…”
Section: Discussionmentioning
confidence: 99%
“…5,29,30 Irrespective of these recommendations there is currently limited evidence comparing the 2 agents. 15,[31][32][33] Therefore, the aim of this retrospective cohort is to compare hemostatic efficacy and safety outcomes between andexanet alfa and 4F-PCC for reversal of FXa-inhibitor-related bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Culbreth et al did studies also done by Brown et al and two studies in 2018, and 2019 had zero incidences of thrombotic events [ 20 , 22 , 23 ]. A retrospective study done by Coleman et al did not include the incidence of thrombotic events [ 19 ]. The most common thrombotic event reported was DVT; 19 out of 48 patients with thromboembolic events had DVT.…”
Section: Reviewmentioning
confidence: 99%
“…The Ammar et al study used different values for hematoma expansion, the Culbreth et al 2018 study reported repeat CT as stable or worsening while the Culbreth et al 2019 study which included patients requiring emergent surgery reported hemostatic effectiveness as per surgeon [ 17 , 22 , 23 ]. Coleman et al did not study hemostatic efficacy while Brown et al evaluated hemostatic efficacy in ICH and surgery requiring patients as hematoma expansion if there was >20% increase in pre-treatment hematoma volume or hematoma diameter [ 19 , 20 ]. ANNEXA-4 trial and the Steven et al study evaluated hemostatic efficacy by measuring anti-factor Xa activity, at end of 12 hours while 24 hours was used as the time frame in a study by Barra et al and Nederpelt et al [ 18 , 25 ].…”
Section: Reviewmentioning
confidence: 99%